Energy-Efficient APTEEN LoRa Wireless Sensor Network for Soil Moisture Monitoring in Precision Agriculture - Hanugra Aulia Sidharta; Ilham Thoriq Nizar Abadi; Diah Risqiwati; Denar Regata (Prodi Pendidikan Teknik Informatika Universitas Pendidikan Ganesha, 2026)
Precision agriculture requires energy efficient wireless sensor networks (WSNs) that operate reliably over long distances in harsh outdoor environments. This paper presents a field implementation and experimental evaluation of the APTEEN routing protocol on a LoRa RFM95W WSN for soil moisture monitoring in rice fields. The proposed system consists of ESP32 sensor nodes and a sink node, organized into APTEEN clusters and equipped with soil moisture and power monitoring sensors, communicating over LoRa links up to 260 m under non line of sight (NLOS) conditions. The network is evaluated in two configurations, with and without APTEEN, using quality of service (QoS) metrics including latency, throughput, received signal strength indication (RSSI), signal to noise ratio (SNR), energy consumption, and estimated node lifetime. Experimental results show that the APTEEN configuration reduces average current consumption by approximately 2.9% and increases the estimated node lifetime by about 0.7 - 1.1 h for a 3000 mAh battery compared with the non-protocol baseline, while maintaining end to end latency in the range of 1 - 2 s and reliable communication at distances up to 260 m. These findings demonstrate that APTEEN provides modest but measurable improvements in energy efficiency and communication stability in LoRa WSN deployments for real-time soil moisture monitoring in precision agriculture, while also offering preliminary but meaningful evidence from a pilot-scale field validation under constrained deployment conditions.